Farmer’s three fold path for success - Nikhade, Shivam Raju (Indian Farming, 2020)
INDIA’S Agricultural share in economy and population engaged has always been moving in contrary directions. We are in the country where agricultural GDP share was once more than 50% in 1950s and now about 17% despite being not a greater shift of population from agriculture, still we have our half a population engaged in agricultural based activities.